New species of sponges (Porifera, Demospongiae) from the Aleutian Islands and Gulf of Alaska - Lehnert, Helmut; Stone, Robert P. (Zootaxa, 2015)
Ten new species of demosponges, assigned to the orders Poecilosclerida, Axinellida and Dictyoceratida, discovered in the Gulf of Alaska and along the Aleutian Island Archipelago are described and compared to relevant congeners. Poecilosclerida include Cornulum globosum n. sp., Megaciella lobata n. sp., M. triangulata n. sp., Artemisina clavata n. sp., A. flabellata n. sp., Coelosphaera (Histodermion) kigushimkada n. sp., Stelodoryx mucosa n. sp. and S. siphofuscus n. sp. Axinellida is represented by Raspailia (Hymeraphiopsis) fruticosa n. sp. and Dictyoceratida is represented by Dysidea kenkriegeri n. sp. The genus Cornulum is modified to allow for smooth tylotes. We report several noteworthy biogeographical observations. We describe only the third species within the subgenus Histodermion and the first from the Indo-Pacific Region. Additionally, the subgenus Hymerhaphiopsis was previously represented by only a single species from Antarctica. We also report the first record of a dictyoceratid species from Alaska. The new collections further highlight the richness of the sponge fauna from the region, particularly for the Poecilosclerida.